A meta‐analysis reveals global patterns of sediment effects on marine biodiversity. Issue 12 (13th August 2019) - Magris, Rafael A.; Ban, Natalie C.
Abstract: Aim: Sediment disturbances are important threats affecting marine biodiversity, but the variety of biological responses has not yet been synthesized. Here, we collate all available information to compare the extent of impacts across different taxonomic groups, habitat types and pathways of impact (light attenuation, suspended sediment and sedimentation). Location: Global. Time period: Data collected from 1979 to 2017. Major taxa studied: Corals, fishes, seagrasses, sponges, macroalgae, ascidians, bryozoans, crustaceans, echinoderms, molluscs and polychaetes. Methods: We used meta‐analyses to evaluate the effects of sediments across 842 observations found in 110 publications. We also evaluated some of the biological and methodological factors that could explain the variable effects observed in different studies. Results: We found a significant negative effect of sediments on behavioural responses of species, reproduction and recruitment processes, the morphology of organisms, physiology, community abundance and diversity, and species interactions. In contrast, the overall effect on the abundance of individual species was statistically non‐significant and there was a strong positive effect on abundance for sponge and polychaete species. Many individual studies described physiological effects on coral reefs, but the effects on the diversity of soft‐bottom and coral reef communities were particularly detrimental. Phototrophic species were generally more negatively impacted by sediments than heterotrophs, driven by strong physiological responses in crustose coralline algae and seagrasses. Additionally, species with limited mobility were more vulnerable to sediment disturbances than highly mobile species. Sedimentation alone triggered more consistently negative effects on most biological responses than light depletion and suspended sediments. We found evidence for increased impacts on community diversity when more than one pathway of impact was present, indicating that these disturbances can disrupt whole ecosystems. Main conclusions: Our meta‐analysis provided, for the first time, strong quantitative support of negative effects of sediments on marine biodiversity. Taxonomic groups, habitat types and life‐history characteristics were most influential in determining the biological responses to sediment disturbances, highlighting the importance of an ecosystem‐based approach when fully accounting for the impacts of sediments.